2019
DOI: 10.3390/w11112380
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Lake Water Quality and Eutrophication Risk in an Agricultural Irrigation Area: A Case Study of the Chagan Lake in Northeast China

Abstract: Water quality safety is the key factor to maintain the ecosystem service functions of lakes. Field investigations and statistical analyses were carried out to study the water quality of a large, agriculture-stressed lakes (e.g., Chagan Lake) in Northeast China. The hydro-chemical properties of the Chagan Lake are HCO3·CO3-Na. Nutrient (N and P) and non-nutrient (pH and F−) were found to be the major factors that threaten water quality safety of the lake. The concentration of total nitrogen (TN) and total phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 69 publications
(72 reference statements)
4
28
0
2
Order By: Relevance
“…Another interesting finding derived from the sensitivity analysis results is the relatively small increase of Chl-a, which is observed for negative changes of the WT parameter and corresponds to temperatures of less hot months, might be attributed to other meteorological conditions/factors, which exist during spring and autumn. For example, wind mixing is more intense during these seasons and can lead to the release of phosphorus and nitrogen from the sediments, a process which favors eutrophication [59]. In addition, based on the sensitivity analysis results, it is concluded that the EC parameter role is not easy to be understood, since it is associated with complex processes such as wind mixing and inorganic dissolved matter inflow from the lake's catchment, e.g., surface runoff and river inflow [60].…”
Section: Discussionmentioning
confidence: 99%
“…Another interesting finding derived from the sensitivity analysis results is the relatively small increase of Chl-a, which is observed for negative changes of the WT parameter and corresponds to temperatures of less hot months, might be attributed to other meteorological conditions/factors, which exist during spring and autumn. For example, wind mixing is more intense during these seasons and can lead to the release of phosphorus and nitrogen from the sediments, a process which favors eutrophication [59]. In addition, based on the sensitivity analysis results, it is concluded that the EC parameter role is not easy to be understood, since it is associated with complex processes such as wind mixing and inorganic dissolved matter inflow from the lake's catchment, e.g., surface runoff and river inflow [60].…”
Section: Discussionmentioning
confidence: 99%
“…The lake is surrounded by three irrigation districts, including an old irrigation district (Qianguo district) and two new irrigation districts (Da'an and Qian'an districts) covering 5.07 × 10 4 , 2.19 × 10 4 and 1.33 × 10 4 hectares, respectively (Figure 1). As the lake receives discharge from the Qianguo and Da'an irrigation districts, nutrients, salt, and alkali flowing into the lake have caused eutrophication and salinity to increase [61,62]. According to the development plan of the Songyuan irrigation district, 'the irrigation discharge from the Qian'an irrigation district will flow into Chagan Lake in the future.…”
Section: Study Areamentioning
confidence: 99%
“…Based on this classification, Chagan Lake may eventually evolve from a freshwater lake to sub-saline lake, similar to the process of salinization of the Boston Lake [28,51]. However, the depth of Chagan Lake is less than Boston Lake [51,61], hence the ecosystem of Chagan Lake is more vulnerable to water salinization. The fish community structure and production are limited by the increased salinity of the lake because higher salinity can inhibit fish embryos from hatching and can reduce plankton production [90,93].…”
Section: The Effect Of Salinization On Lake Ecosystem Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Chagan Lake is located in the western part of Jilin Province, which is the drainage area for the commodity grain production base. Drainage from the surrounding irrigation fields is the major water source of the lake, accounting for 63.4% of all water sources [20]. According to the Special Plan for Ecological and Environmental Protection of the Chagan Lake Basin, the area of irrigated high-standard farmland in Jilin Province has continued to grow since 2006, and the intensity of water supply and drainage in the irrigation area has been continuously increasing.…”
Section: Study Areamentioning
confidence: 99%